THE DETERMINANTS OF FIRM VALUE - Warsiki, Luh Ketut Kumari Chandra; Dewi, Sofia Prima (International Journal of Application on Economics and Business, 2023)
This research aims to obtain empirical evidence about the impact of leverage, profitability, firm size, and dividend policy toward the firm value of non-cyclical firms which is listed on the Indonesia Stock Exchange from period of 2018-2020. Using purposive sampling method, the sample in this study were 21 non-cyclical companies. The multiple linear regression model is used in this research and processing data with E-views 12 SV. In this research, firm value as dependent variable measures with a Price to Book Value. The result concludes that dividend policy and profitability impact positively toward firm value, firm size has no impact toward firm value with negative direction, and leverage has no impact toward firm value with positive direction.